Odontogenic myxoma in childhood - Ana Cláudia Garcia Rosa; Cristiano Abdalla Rosa; Eduardo Zambaldi da Cruz; Fabiana Ferreira Alves; André Machado de Senna (Elsevier, 2023)
Odontogenic myxoma is a benign odontogenic tumor of ectomesenchymal origin. In adults, it is the third most frequent odontogenic tumor, but in children, this tumor is uncommon. This paper aims to report an uncommon case of an odontogenic myxoma in a 10-year-old girl. The patient was referred to a children's hospital presenting with asymptomatic facial asymmetry, noticed six months earlier. Intraoral examination showed a tumoral lesion in the right posterior maxillary region, with an expansion of the buccal bone plate, without ulceration or mucosal color change. Computed tomography revealed a hypodense lesion with extensive bone involvement in the right maxillary region, with the displacement of the tooth germ of the upper right third molar, involving the maxillary sinus, orbital floor, and nasal cavity. An incisional biopsy was performed. Gross examination revealed a grayish-white lesion, with a firm-elastic consistency. The histological sections revealed a non-encapsulated neoplasm formed by spherical and spindle-shaped cells, with a stellate arrangement in a myxoid stroma with variable amounts of collagen. There was no evidence of odontogenic epithelium. The diagnosis was odontogenic myxoma. An enucleation with vigorous curettage of the margins of the lesion was performed, and no recurrence was observed in two years of postoperative follow-up.